Analisis Pelaksanaan Pengawasan DLH Surakarta Terhadap Pengelolaan Limbah B3 di RSUD Dr. Moewardi Kota Surakarta - Muhammad Fikri Haikal; Rahayu Subekti; Purwono Sungkowo Raharjo (PLEDOI (Jurnal Hukum dan Keadilan), 2024)
This study aims to examine the implementation of the supervisory function of the Surakarta City Environment Service (DLH) on the Management of Hazardous and Toxic Waste (B3) RSUD Dr. Moewardi and obstacles in implementing the supervisory function. This research is an empirical legal research and is descriptive in nature. This study uses a qualitative approach with data sources in the form of primary data sources and secondary data sources. Data collection techniques used were document studies and interviews. The data analysis technique used is qualitative data analysis. The results of the study show that the implementation of the supervisory function of the Surakarta City Environmental Service (DLH) on B3 Waste Management at RSUD Dr. Moewardi has not been carried out optimally because DLH Surakarta in carrying out field supervision is not carried out completely and thoroughly according to Standard Operating Procedures (SOP) because supervision is only based on glimpses of the waste storage location and questions and answers only so there is concern that there will be discrepancies in the results of the written report with the actual situation in field. The obstacles faced by DLH Surakarta in carrying out the supervisory function are due to a lack of human resources making it difficult to divide schedules and supervise many agencies so that there are agencies that do not receive maximum supervision, the budget is very minimal so it is difficult to finance supervisory activities, and the facilities and infrastructure are inadequate.